Gender asymmetry in verbal, visual and logical-mathematical abilities - Dadashova Aidan Guliaddin (Technium Social Sciences Journal, 2020)
The aim of the study is to assess verbal, visual and logical-mathematical abilities based on socio-psychological methods at the gender level, to study ways of regulating cognitive capabilities in the education system within the framework of gender equality and to analyze them from a socio-psychological point of view. The research methodology is based on psychological, pedagogical, sociological and cultural concepts, gender theories and theories of feminism, biodeterministics approaches and approaches to gender differentiation. The scientific novelty of the research is the socio-psychological assessment of verbal, visual and logical-mathematical abilities in the educational process at the level of gender asymmetry, identifying their causes and results. Output. Gender differences appear in the physical, psychological, behavioral and cognitive areas. There are differences in the verbal, visual, logical and mathematical abilities of the sexes in education. As a result of a comparative analysis of both approaches, we came to the conclusion that the differences in the verbal, visual, logical-mathematical abilities of the sexes observed in education have a kind of influence of both ontogenetic and gender roles. These influences usually act syncretically rather than autonomously. Therefore, researchers argue about their origin. However, recent research suggests that the perceived underdevelopment of girls’ logical and mathematical abilities is in fact related to gender. That is, traditional pedagogy and family environment play an important role in the emergence of such stereotypes.